The impact of timolol maleate on the ocular tolerability of fixed-combination glaucoma therapies - Radcliffe NM (Dove Medical Press, 2014)
Nathan M Radcliffe Ophthalmology, New York University, New York, NY, USA Abstract: Glaucomatous optic atrophy is the second most common cause of blindness worldwide, and lowering intraocular pressure (IOP) is the only proven method to slow or stop the progression of the disease. Approximately 40% of patients with elevated IOP will require more than one medication to obtain a modest 20% reduction in IOP, and as a result, some patients may require two medications, provided in either two separate bottles or in one bottle with the use of fixed-combination therapies. Each therapy has its own unique safety and efficacy profile. Topical beta-blockers have a particularly favorable ocular-tolerability profile, and several studies of fixed-combination medications containing the beta-blocker timolol maleate have shown a lower prevalence of some ocular adverse events for the fixed-combination therapy compared to the non-beta-blocker individual component. In this review, we examined clinical data pertaining to the ocular surface tolerability of fixed-combination medications containing timolol maleate in comparison to the individual components. In particular, preference was given to prospective, randomized, multicenter trials of 3 months in duration or longer that compared a fixed-combination therapy to monotherapy with the individual components. A review of the literature revealed that some fixed-combination therapies can provide a reduced risk of common side effects compared to their individual components, with conjunctival hyperemia and ocular allergy being less frequent in some timolol-containing fixed-combination therapies. This effect appears to be most significant for latanoprost 0.005%, bimatoprost 0.03%, and brimonidine 0.2%. Keywords: bimatoprost, brimonidine, hyperemia, latanoprost, ocular allergy